The influence of surface soil physicochemistry on the edaphic bacterial communities in contrasting terrain types of the Central Namib Desert. Issue 5 (4th May 2015) - Gombeer, S.; Ramond, J.‐B.; Eckardt, F. D.; Seely, M.; Cowan, D. A.
Abstract Notwithstanding, the severe environmental conditions, deserts harbour a high diversity of adapted micro‐organisms. In such oligotrophic environments, soil physicochemical characteristics play an important role in shaping indigenous microbial communities. This study investigates the edaphic bacterial communities of three contrasting desert terrain types (gravel plains, sand dunes and ephemeral rivers) with different surface geologies in the Central Namib Desert. For each site, we evaluated surface soil physicochemistries and used explorative T‐RFLP methodology to get an indication of bacterial community diversities. While grain size was an important parameter in separating the three terrain types physicochemically and specific surface soil types could be distinguished, the desert edaphic bacterial communities displayed a high level of local spatial heterogeneity. Ten variables contributed significantly (P < 0.05) to the variance in the T‐RFLP data sets: fine silt, medium and fine sand content, pH, S, Na, Zn, Al, V and Fe concentrations, and 40% of the total variance could be explained by these constraining variables. The results suggest that local physicochemical conditions play a significant role in shaping the bacterial structures in the Central Namib Desert and stress the importance of recording a wide variety of environmental descriptors to comprehensively assess the role of edaphic parameters in shaping microbial communities.